Synthesis and CNS Depressant Activity of Some New Mannich Bases of 1-(4-Dimethylamino)phenyl-4-methyl-pent-1-en-3-one - Rajasekaran, A.; Murugesan, S. (Asian Journal of Chemistry, 2016)
4-Dimethylaminobenzaldehyde was condensed with 2-butanone in presence of 10% sodium hydroxide to yield 1-(4-dimethylamino) phenyl-4-methyl-pent-1-en-3-one (I). Six new mannich bases have been synthesized by the interaction of 1 with six different secondary amines in the presence of paraformaldehyde. All the synthesized compounds were characterized by IR and 1H-NMR spectra and evaluated for CNS depressant activity.